2021
DOI: 10.1007/s00125-021-05525-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of enterovirus RNA detected in the pancreas and other specimens of live patients with newly diagnosed type 1 diabetes in the DiViD study

Abstract: Aims/hypothesis The Diabetes Virus Detection (DiViD) study is the first study to laparoscopically collect pancreatic tissue and purified pancreatic islets together with duodenal mucosa, serum, peripheral blood mononuclear cells (PBMCs) and stools from six live adult patients (age 24–35 years) with newly diagnosed type 1 diabetes. The presence of enterovirus (EV) in the pancreatic islets of these patients has previously been reported. Methods In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
5
24
0
Order By: Relevance
“…The low amount of virus in the pancreatic islets of patients with T1D implies a low-grade enteroviral persistent infection rather than acute infection ( Krogvold et al., 2015 ). This was further supported by our recent study that revealed low levels of enterovirus strains in the purified islets that were different from the strains simultaneously detected in stools, blood, duodenal biopsy, and/or the whole pancreas tissue in the same patient with T1D ( Oikarinen et al., 2021 ). The association between CVBs and T1D has been emphasized by prospective birth cohort studies ( Laitinen et al., 2014 ; Oikarinen et al., 2014 ; Sioofy-Khojine et al., 2018 ; Vehik et al., 2019 ).…”
Section: Introductionsupporting
confidence: 65%
“…The low amount of virus in the pancreatic islets of patients with T1D implies a low-grade enteroviral persistent infection rather than acute infection ( Krogvold et al., 2015 ). This was further supported by our recent study that revealed low levels of enterovirus strains in the purified islets that were different from the strains simultaneously detected in stools, blood, duodenal biopsy, and/or the whole pancreas tissue in the same patient with T1D ( Oikarinen et al., 2021 ). The association between CVBs and T1D has been emphasized by prospective birth cohort studies ( Laitinen et al., 2014 ; Oikarinen et al., 2014 ; Sioofy-Khojine et al., 2018 ; Vehik et al., 2019 ).…”
Section: Introductionsupporting
confidence: 65%
“…In a study from Norway (the Diabetes Virus Detection (DiViD) study), enterovirus B RNA was predominantly detected in purified pancreatic islets and duodenal mucosa from biopsy samples, peripheral blood mononuclear cells and stool samples from six adult patients with T1DM 37 . However, no islet-resident enteroviruses could be isolated using permissive cell lines 37 , which suggests defective or slowed viral replication of these viruses 53 . This finding is consistent with the idea of persistent infection in the pancreas of patients with T1DM 32 .…”
Section: Enterovirus Persistence In T1dmmentioning
confidence: 99%
“…The enteroviral genome found in the pancreas of patients with T1DM has been sequenced. Sequences of enteroviruses other than CVB were identified in some patients, but due to the low level of viral RNA, the exact genotype of the virus was not identified 37 .…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with in vitro studies showing that increased expression of MDA5 is also driven by pro-inflammatory molecules. Of note, it has been demonstrated that exposure of pancreatic islet cells to viruses or to viral intermediates (dsRNAs) leads to MDA5 increased expression ( 16 , 20 ); remarkably, evidence of EV infection has been detected in the pancreatic islets of all DiViD cases across different laboratories employing multiple approaches ( 6 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among identified environmental factors, viral infections have been undoubtedly shown to play a prominent role (2,3). As a matter of fact, multiple evidences of Enterovirus infection of pancreatic islets in T1D donors have now been confirmed by several studies, also adopting rigorous methodological cross-validation approaches in various patient cohorts (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%